Including youth in agriculture through extension and advisory services - Davis, Kristin E.; Franzel, Steven; Luzobe, Beatrice; Miiro, Richard; Rurangwa, Raphael; Uwitonze, Nicolas (United States Agency for International Development, 2020)
In Africa south of the Sahara, more than 12 million new jobs a year are needed in rural areas to absorb young entrants. Agriculture provides scalable economic opportunities that can also reduce poverty. Engaging youth in extension and advisory services (EAS) can help address the employment challenge and contribute to economic development — by recruiting young people as providers and/or helping larger numbers of youth access services needed for them to engage in successful agricultural livelihoods. But little is known about how to engage youth in EAS, especially in the private sector.